2010
DOI: 10.1038/onc.2010.436
|View full text |Cite
|
Sign up to set email alerts
|

Integration of cap analysis of gene expression and chromatin immunoprecipitation analysis on array reveals genome-wide androgen receptor signaling in prostate cancer cells

Abstract: The androgen receptor (AR) is a critical transcriptional factor that contributes to the development and the progression of prostate cancer (PCa) by regulating the transcription of various target genes. Genome-wide screening of androgen target genes provides useful information to understand a global view of AR-mediated gene network in PCa. In this study, we performed 5'-cap analysis of gene expression (CAGE) to determine androgen-regulated transcription start sites (TSSs) and chromatin immunoprecipitation (ChIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
110
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(115 citation statements)
references
References 44 publications
2
110
3
Order By: Relevance
“…In contrast to previous CAGE studies by the Genome sequencer FLX system (454) 48 , we observed 57% of the signals within 500 bp of the 5 0 -ends of messenger RNAs based on the genomic coordinates of the reference full-length transcripts of RefSeq. We aggregated neighbouring CAGE tags on the genome into TCs and obtained 19,644 TCs.…”
Section: Methodscontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to previous CAGE studies by the Genome sequencer FLX system (454) 48 , we observed 57% of the signals within 500 bp of the 5 0 -ends of messenger RNAs based on the genomic coordinates of the reference full-length transcripts of RefSeq. We aggregated neighbouring CAGE tags on the genome into TCs and obtained 19,644 TCs.…”
Section: Methodscontrasting
confidence: 99%
“…For ChIP using AR, FOXA1 and TET2 antibody, cells were crosslinked with 1% formaldehyde for 10 min and stopped by adding 0.2 M glycine. Cells were lysed by lysis buffer 48,49 and chromatin DNA was sheared by sonication. Sonicated lysates were incubated overnight at 4°C with specific antibodies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A modest overexpression of AR enhances the chromatin binding of the receptor by sensitizing the cells to 100-fold lower ligand concentration. The majority of the previously reported ChIP-seq and ChIP-chip experiments (Jia et al, 2008;Wang et al, 2009;Takayama et al, 2010;Yu et al, 2010) have compared the binding of AR at the saturating concentration of androgens, and thus, missed the dynamics of AR binding. However, our data are in line with a recent work by Massie et al (2011), in which they found almost five times more ARBSs in the strongly AR-overexpressing cell line VCaP compared with LNCaP cells.…”
Section: Discussionmentioning
confidence: 99%